A course on plasticity theory - Steigmann, David J. 1956- (Oxford University Press, 2022)
Plasticity Theory is characterized by many competing and often incompatible points of view. This book seeks to strengthen the foundations of continuum plasticity theory, emphasizing a unifying perspective grounded in the fundamental notion of material symmetry. Steigmann's book offers a systematic framework for the proper understanding of established models of plasticity and for their modern extensions and generalizations. Particular emphasis is placed on the differential-geometric aspects of the subject and their role in illuminating the conceptual foundations of plasticity theory. Classical models, together with several subjects of interest in contemporary research, are developed in a unified format. The book is addressed to graduate students andacademics working in the field of continuum mechanics
Keywords: bicssc / Mechanical engineering; bicssc / Materials science; Plastizitätstheorie